Answer:
The answer to your question is
![((x - 2)^(2) )/(4) - ((y - 1)^(2))/(5) = 1](https://img.qammunity.org/2020/formulas/mathematics/high-school/xttog8wvxtujc54hr9a4cs7ajf56feja5t.png)
Explanation:
Data
Foci (-1, 1) and (5, 1) [A and B]
Vertices (0, 1) and (4, 1) [C and D]
See the image below. From the image we can conclude that it is a horizontal hyperbola.
Equation
![((x - h)^(2) )/(a^(2) ) - ((y - k)^(2) )/(b^(2) ) = 1](https://img.qammunity.org/2020/formulas/mathematics/high-school/w8ivc966w2s7utkmy9mec65faspb88mrxx.png)
From the image calculate the center
The center is in the middle of the vertices (2, 1)
Now, calculate a, a is the distance from the center to the vertices, a = 2
Calculate c, c is the distance from the center to the foci, c = 3
Calculate b with the pythagorean theorem c² = a² + b²
b² = c² - a²
b² = 3² - 2²
b² = 9 - 4
b² = 5
Substitution
![((x - 2)^(2) )/(4) - ((y - 1)^(2))/(5) = 1](https://img.qammunity.org/2020/formulas/mathematics/high-school/xttog8wvxtujc54hr9a4cs7ajf56feja5t.png)